Cryptography theory and practice - Stinson, Douglas R. (Douglas Robert) 1956- (CRC Press series on discrete mathematics and its applications, 2006)
"The art and science of cryptography has been evolving for thousands of years. Now, with unprecedented amounts of information circling the globe, we must be prepared to face new threats and employ new encryption schemes on an ongoing basis. This edition updates relevant chapters with the latest advances and includes seven additional chapters covering: pseudorandom bit generation in cryptography; entity authentication, including schemes built from primitives and special purpose zero-knowledge schemes; key establishment including key distribution and protocols for key agreement, both with a greater emphasis on security models and proofs; public key infrastructure, including identity-based cryptography; secret sharing schemes; multicast security, including broadcast encryption and copyright protection."--Book cover